Spanish I Beginning Spanish Language and Culture - Dean, Matthew; Open Textbook Library (Open Textbook Library, 2020)
This peer-reviewed textbook is designed for the true beginner with U.S. college students in mind. It contains themed chapters, which are divided into 8 sections. Each section has its own set of learning objectives, and is further separated into three types of assignments, Para estudiar en casa (with detailed explanations), Para practicar en casa (homework exercises), and Para practicar en clase (paired and group classwork activities). The explanations and primary input are written to be easily comprehensible. The individual exercises are geared towards acquisition of form and function, and the communicative classwork exercises promote interpersonal exchanges between students. The digital copy includes some embedded audio files, and we are developing a website to house many more resources.
1.En la universidad -- 2. La familia -- 3.En casa -- 4.De compras -- 5.Los pasatiempos
In English.
Description based on online resource
Keywords: Humanities -- Textbooks; Language and languages -- Textbooks